Evaluation of the responsiveness of the Iranian health system to the needs of the elderly during the COVID-19 pandemic: a community-based study - Sepideh Niazie; Heshmatolah Heydari; Hadi Hayati; Ali Dehghani (BMC Health Services Research)
Abstract Background The elderly population is growing globally. As a vulnerable part of society, the elderly are exposed to more harm when facing pandemics of infectious diseases, so the quality of the health system’s response is critical for these individuals. Considering a paucity of studies in this area, this research assessed the responsiveness of the Iranian health system to the needs of the elderly during the COVID-19 pandemic. Methods This cross-sectional descriptive-analytical study was conducted on 259 elderly at the Lorestan University of Medical Sciences from April to September 2022. A combination of stratified multi-stage cluster systematic sampling, was used to recruit participants. The WHO Multi-country Survey Study on Health and Responsiveness was used for data collection. Data were analyzed by using SPSS v.24 software and descriptive/inferential statistics such as the Kolmogorov–Smirnov test, Pearson correlation, independent t-test, ANOVA, and multivariate regression at the statistical significance level of P <.05. Results The data analysis revealed that the overall responsiveness of Iran’s health system was average (79.99 ± 11.4). The best dimension of responsiveness was access to family support (10.17 ± 1.3), and autonomy was the weakest (7.46 ± 2.5). According to multiple linear regression analysis, the variables of age, gender, education level, medical history, number of children, marital status, and monthly income had a significant relationship with the total health responsiveness score (P <.005). According to the adjusted R2 of 0.94, this regression model was able to explain 94% of variations in the mean total responsiveness score. Conclusion The results showed that the Iranian health system’s performance in responding to the needs of the elderly during the COVID-19 pandemic was acceptable. These findings can help the health system promote its responsiveness during future epidemics and pandemics and better fulfill the needs of the elderly. Since infrequent studies are available in this field, various dimensions of responsiveness are suggested to be investigated more deeply.